Necroptosis Is Involved in CD4+ T Cell-Mediated Microvascular Endothelial Cell Death and Chronic Cardiac Allograft Rejection. Issue 9 (September 2017) - Kwok, Cecilia; Pavlosky, Alexander; Lian, Dameng; Jiang, Jifu; Huang, Xuyan; Yin, Ziqin; Liu, Weihua; Haig, Aaron; Jevnikar, Anthony M.; Zhang, Zhu-Xu
Abstract : Background: Despite advances in immunosuppressive therapies, the rate of chronic transplant loss remains substantial. Organ injury involves various forms of cell death including apoptosis and necrosis. We now recognize that early injury of cardiac transplants involves a newly described form of programmed necrotic cell death, termed necroptosis. Because this involves receptor-interacting protein (RIP) kinase 1/3, this study aimed to establish the role of RIP3 in chronic cardiac allograft rejection. Methods: We used major histocompatibility complex class II mismatched C57BL/6N (H-2 b ; B6) or B6.RIP3 −/− (H-2 b ; RIP3 −/− ) mice to B6.C-H-2 bm12 (H2-Ab1 bm12 ; bm12) mouse cardiac transplantation. Microvascular endothelial cells (MVEC) were developed from B6 and RIP3 −/− cardiac grafts. Result: CD4 + T cell–mediated cardiac graft rejection is inhibited using RIP3 deficient donor grafts, with reduced cellular infiltration and vasculopathy compared with wild type cardiac grafts. Alloreactive CD4 + T cell–mediated MVEC death involves TNFα, Fas ligand (FasL) and granzyme B. Although necroptosis and release of danger molecule high-mobility group box 1 are eliminated by the absence of RIP3, CD4 + T cells had attenuated MVEC death through granzyme B and FasL. Conclusions: CD4 + T cell–mediated MVEC death involves in TNFα, FasL and granzyme B. Necroptotic cell death and release of the danger molecule may promote inflammatory responses and transplant rejection. Although loss of RIP3 does not eliminate alloimmune responses, chronic graft injury is reduced. RIP3 is an important therapeutic target but additional granzyme and caspases inhibition is required for sufficiently improving long-term graft survival. Abstract : Kwok et al report that necroptic endothelial cell death results in the release of HMGB1 that promotes inflammatory responses, and when necroptic death is prevented by RIP3 deficiency in combination with granzyme and caspase inhibition, allograft survival is improved.